Dragonfire - Bell, Ted (Bell, Ted. Alex Hawke novel, 2020)
December 8, 1941, Washington, D.C: The new Chinese ambassador to the United States, Tiger Tang, meets with President Roosevelt one day after the Japanese attack Pearl Harbor. China and the U.S. are wartime allies, but the Chinese ambassador may be playing his own treacherous game, including an assassination plot that could well change the course of history. Present day, the Bahamas: Alex Hawke receives a desperate call from the Queen. Her favorite grandson has disappeared in the Bahamas and Lord Hawke is the only man she trusts with the retrieval mission. The young prince was last seen at the ultra-exclusive Dragonfire Resort, owned by Tiger Tang's twin grandsons, heads of the Tang Dynasty's worldwide criminal enterprise. Hawke battles to unravel a shadowy conspiracy that may be centuries old. -- adapted from jacket